Transplantid.net: A Pilot Crowdsourced, Living, Online Library of Resources for the Teaching and Practice of Transplant Infectious Diseases. (14th February 2023) - Puius, Yoram A; Azar, Marwan M; Tsai, Helen; Vergidis, Paschalis; Harris, Courtney E; Anjan, Shweta; Barros, Nicolas; Belga, Sara; Chuang, Sally T; Czeresnia, Jonathan M; Goel, Shipra; Ince, Dilek; et al.
Abstract: The field of transplant infectious diseases is rapidly evolving, presenting a challenge for clinical practice and trainee education. Here we describe the construction of transplantid.net, a free online library, crowdsourced and continuously updated for the dual purpose of point-of-care evidence-based management and teaching. Abstract : We describe the inception of http://transplantid.net, a free online transplant infectious diseases bibliography for patient care and teaching. It is constructed with free resources, crowdsourced and continuously updated. This model can be generalized to any rapidly evolving field.